Impact of baseline HIV‐1 RNA levels on initial highly active antiretroviral therapy outcome: a meta‐analysis of 12, 370 patients in 21 clinical trials1. Issue 5 (22nd November 2012) - Stephan, C; Hill, A; Sawyer, W; van, Y; Moecklinghoff, C
<x xml:space="preserve">Abstract</x> Background Individual randomized trials of first‐line antiretroviral treatment do not consistently show an association between higher baseline HIV‐1 RNA and lower efficacy. Methods A MEDLINE search identified 21 HIV clinical trials with published analyses of antiretroviral efficacy by baseline HIV‐1 RNA, using a standardized efficacy endpoint of HIV‐1 RNA suppression <50 copies/mL at week 48. Results Among 21 clinical trials identified, eight evaluated only nonnucleoside reverse transcriptase inhibitor (NNRTI)‐based combinations, eight evaluated only protease inhibitor‐based regimens and five compared different treatment classes. Ten of the trials included tenofovir (TDF)/emtricitabine (FTC) as only nucleoside reverse transcriptase inhibitor (NRTI) backbone, in addition but not restricted to abacavir (ABC)/lamivudine (3TC) (n = 7), zidovudine (ZDV)/3TC (n = 4) and stavudine (d4T)/3TC (n = 1). Across trials, the mean percentage of patients achieving HIV‐1 RNA < 50 copies/mL at week 48 was 81.5% (5322 of 6814) for patients with baseline HIV‐1 RNA < 100 000, vs. 72.6% (3949 of 5556) for patients with HIV‐1 RNA > 100 000 copies/mL. In the meta‐analysis, the absolute difference in efficacy between low and high HIV‐1 RNA subgroups was 7.4% [95% confidence interval (CI) 5.9–8.9%; P < 0.001]. This difference was consistent in trials of NNRTI‐based treatments (difference = 6.9%; 95% CI 4.3–9.6%), protease inhibitor‐based treatments (difference = 8.4%; 95% CI 6.0–10.8%) and integrase or chemokine (C‐C motif) receptor 5 (CCR5)‐based treatments (difference = 6.0%; 95% CI 2.1–9.9%) and for trials using TDF/FTC (difference = 8.4%; 95% CI 6.0–10.8%); there was no evidence for heterogeneity of this difference between trials (Cochran's Q test; not significant). Conclusions In this meta‐analysis of 21 first‐line clinical trials, rates of HIV‐1 RNA suppression at week 48 were significantly lower for patients w ith baseline HIV‐1 RNA > 100 000 copies/mL (P < 0.001). This difference in efficacy was consistent across trials of different treatment classes and NRTI backbones.